THE RELATIONSHIP BETWEEN VOCATIONAL PROFICIENCY AND ENTREPRENEURSHIP ACCORDING TO GIRLS’ VOCATIONAL HIGH SCHOOL STUDENTS’ PERCEPTIONS - Tan, Çetin; Çankaya, İbrahim (My University, 2018)
The purpose of this study is to compare perceptions of girls’ vocational high schoolstudents about vocational proficiency and entrepreneurship with respect to attendanceto practical training. This study utilizes relational screening model. The universe of thestudy consists of the students of Uşak Central Anatolian Vocational and Girls’ VocationalSchools in 2014-15 school year. No sampling was done for the study as the scale wasapplied to all of the students studying at child development, beauty and hair care, andtextile technologies departments. 98 Twelfth graders who have attended to practicaltraining and 70 ninth graders who have not attended have been classified separately.Data has been collected by using two different scales. One of these scales is vocationalproficiency scale developed by Bozgeyikli. The other scale used, entrepreneurship scale,is a five level Likert-type scale developed by Yılmaz & Sümbül. It has been found outthat there is a significant difference about vocational proficiency perceptions betweenthe students who have attended practical training and those who have not attended. Itwas revealed that the students who have attended practical training have more positiveperceptions towards vocational proficiency ( with respect to those who havenot attended . When compared to the students who have not attended, thestudents who have attended to practical training had significant difference in theirperception of entrepreneurship. The attending students of practical traininghave a higher tendency towards entrepreneurship with respect to those who have notattended . The students’ opinions also reveal that there is a high andsignificant relationship between tendency towards entrepreneurship and perception ofvocational proficiency.
Keywords: Eğitim; Eğitim Araştırmaları; İşletme; Endüstri Mühendisliği